Microalgal colony blot: A simple and rapid method for direct detection of recombinant protein production in microalgae colonies - Yasin Torres-Tiji; Francis J. Fields; Stephen P. Mayfield (PLoS ONE, 2026)
Microalgae have emerged as a versatile biotechnological platform, promising to become an efficient source of commodities such as food, feed, and biofuels, but these organisms have also sparked profound scientific and commercial interest for their potential in producing high-value recombinant proteins. Recombinant gene expression is highly dependent on the loci in which the transgene integrates, and in green algae transgenes integrate randomly into the nuclear genome, mostly through non homologous end joining. Therefore, recombinant gene expression varies greatly among different algal transformants and many algal colonies must be screened before a suitable production strain can be found, which can be quite laborious and become a bottleneck in the recombinant strain production pipeline. Here we describe a method for mid-throughput screening of recombinant protein expression; the Microalgal Colony Blot. This screening method allows for the detection of recombinant protein expression in up to 100 algal colonies per petri dish, with each petri dish preparation taking only 20 minutes. A nitrocellulose membrane is layered on top of a petri dish containing agar media, and algal cells are inoculated on top of the filter in a liquid suspension using a micropipette. The colonies are allowed to grow for up to 7 days, with the colonies secreting recombinant protein (either through active secretion or through cell lysis) as they grow with the recombinant protein being immediately bound by the nitrocellulose membrane. After the incubation period, the membrane is treated like a regular western blot, with blocking, washing, antibody binding and visualization. In this manner, up to 1000 colonies can be comfortably screened per day by a single person. Knowing that in C. reinhardtii only about 5% of the transgenic colonies from a transformation produce significant recombinant protein expression, being able to screen 1000 colonies ensures that around 50 suitable candidates will be identified within a single day.